2018
DOI: 10.1111/ggi.13327
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and psychological effects of gardening activity in older adults

Abstract: Our research suggests that gardening activities might enhance physiological and psychological relaxation in older adults. Geriatr Gerontol Int 2018; 18: 1147-1152.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 25 publications
4
34
0
1
Order By: Relevance
“…Systolic blood pressure reduction indicates a state of calmness and lack of trauma in older adults. Our findings are broadly consistent with other experiments that examined physiological responses of older adults to gardening activity (Hassan et al, ). Various clinical and laboratory studies have found that visual stimulation via plants for <5 min has a positive impact on health, such as by reducing blood pressure, heart rate, and muscle tension (Ulrich, , ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Systolic blood pressure reduction indicates a state of calmness and lack of trauma in older adults. Our findings are broadly consistent with other experiments that examined physiological responses of older adults to gardening activity (Hassan et al, ). Various clinical and laboratory studies have found that visual stimulation via plants for <5 min has a positive impact on health, such as by reducing blood pressure, heart rate, and muscle tension (Ulrich, , ).…”
Section: Discussionsupporting
confidence: 92%
“…It is the most accepted and accurate method of assessing stress via brain activity. De Waard () noted that EEG frequencies are usually considered in five different groups: delta waves (4 Hz), alpha waves (8–13 Hz), theta waves (4–8 Hz), beta waves (above 13 Hz), and gamma waves (31–42 Hz; Hassan, Qibing, & Tao, ). Each range behaves differently according to various conditions; for example, during a state of workload or stress, alpha waves disappear while beta waves increase in prominence (Angelucci et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the data is still not extensive, there is a greater evidence-base for benefits associated with communal gardening. These include improvements in: physiological relaxation ( Hassan, Qibing, & Tao, 2018 ), stress relief ( Genter, Roberts, Richardson, & Sheaff, 2015 ), mental health ( Soga, Gaston, & Yamaura, 2017b ), mood ( Grahn & Stigsdotter, 2010 ), social skills ( Himmelheber, Mozolic, & Lawrence, 2018 ), self-esteem ( Cammack, Waliczek, & Zajicek, 2002 ), confidence ( Eum & Kim, 2016 ), creativity ( Exner & Schützenberger, 2018 ), diet ( Hale et al, 2011 ), and opportunity for physical exercise ( Soga et al, 2017a ). Although it would be logical to assume that benefits associated with communal gardening translate across to residential gardening ( Cervinka et al, 2016 ), this needs testing, not least as a number of reports suggest that much of the benefits of communal gardening relate to social interactions, encouragement from peers and pride in producing produce.…”
Section: Introductionmentioning
confidence: 99%
“…To understand an individual's current psychological response state, it is possible to measure changes in the reflex potential produced by the activity of nerve cells in the brain [ 30 ]. It is known that alpha waves are related to a relaxed state [ 30 , 31 ]; however, when mental stress or workload is reduced, alpha waves increase [ 32 ]. Indeed, Hassan et al (2018) [ 31 ] found that participants observing photos of natural landscapes experiences enhanced brain electrical activity in the form of alpha waves.…”
Section: Introductionmentioning
confidence: 99%